Fresno County Women Lawyers' Installation of Officers Dinner Meeting - Watkins, Howard::::::::: (1988)
Sandra Snyder-Hylton, Karen Burt, Ruth Ratzlaff, Doris Coleman, California Women Lawyers Executive Director Katy Sorenson, Hon. Herbert Levy, and California Women Lawyers President Pauline Weaver holding her T-Rex Gift was in reference to Pauline's California Women Lawyers pledge to help lift women out of the dinosaur age